From Panama to San Andres: Mutations in Colombian Foreign Policy - Sánchez, Fabio (2014)
Colombian foreign policy has gone through important transformations in its formulation and implementation. Through a Neoclassical Realist (NCR) analysis, this article discusses the domestic and systemic factors that have influenced the Foreign Policy Executive (FPE) in Colombia. It makes a historical journey through different presidential terms, ranging from the loss of Panama in 1903, to the adverse decision of the International Court of Justice (ICJ) in 2012, which stripped Bogotá of a significant portion of its Caribbean Sea. This analysis reveals problems in the formulation of Colombian foreign policy due to a weak foreign service, a complex relationship with the United States and the country’s internal conflict; it is argued that if these factors were to be reduced or disappear, a new form of foreign policy in the country would be facilitated in the twenty-first century.